(3GdHUGFQ hGdPNGFQs - (3Ydj Hf eMeO Hf GdYHGS GdJhMjOj, CHh MjGf,J (B400 (3g` s ((3jhSa Hf eMeO GdTgjQ HGHf Gdhcjd s)
(3ChdgG (B:s
(3Gddgf Zfc GdMb GdeHjf gPG GdLRA GdKGfi ef HGUFQ GdbOeGA s
(3BNQgG (B:s
(3hKHJc YfO JQGOa GdeMf Ydi efgGLg , hdG CNdGc ef Jhajbg hKeQGJ JMbjbI YfO hLhOg Bejf s
(3GfXQg eY GdLRA GdChd ef faS GdfSNIs
(3ef GdfSNI GdSGHbIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B205 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B684s
Keywords: (3GdCOHs